Reactive oxygen species and anthocyanin are involved in plant response to wounding as part of insect feeding – the case of the somatic hybrids “Solanum tuberosum + Solanum chacoense” - MOLNÁR, Imola; MUSTAȚĂ, Raluca Alina; RAKOSY-TICAN, Elena (Studia Universitatis Babeș-Bolyai Biologia, 2016)
The cultivated potato ranks third in agricultural crop production on global scale. Being the target of attacks by various insects it requires increased attention and protection as well as breeding for resistance. Meanwhile the Colorado potato beetle (Leptinotarsa decemlineata, CPB) has become the biggest enemy of the cultivated potato worldwide. An alternative method of controlling the growth of CPB population would be the use of resistant potato varieties. One of the most effective sources of host-resistance mechanisms is the wild Solanum chacoense. Somatic hybridization via protoplast fusion made it possible the introgression of valuable traits from S. chacoense into cultivated potato. Adequate responses to biotic stresses are crucial for plant survival. The formation of reactive oxygen species during microbial infection is a well-known process but their role against herbivore attacks is still not outlined. The reactive oxygen species (ROS) concentration in plants is controlled by different antioxidative mechanisms in order to maintain the normal function of cells. The aim of our study was to determine the role of ROS signaling as defense response induced by mechanical wounding in potato somatic hybrids. The correlation between CPB resistance and H2O2 accumulation rate were determined, as well. Also the role of anthocyanin as a ROS scavenger was established. Based on our results we conclude that H2O2 accumulation highly influences somatic hybrid response to insect herbivore attacks therefore this type of ROS plays an important role in plant defense mechanism against CPB. Hydrogen peroxide accumulation led to anthocyanin generation therefore anthocyanin plays a role as radical scavenger in potato somatic hybrids. This study is the first to point out the role of reactive oxygen species and anthocyanin biosynthesis in response to mechanical wounding in the somatic hybrids resistant or sensitive to Colorado potato beetle.